Endogenous H2S-Triggered In Situ Synthesis of NIR-II-Emitting Nanoprobe for In Vivo Intelligently Lighting Up Colorectal Cancer - Deng, Zhiming; Jiang, Mingyang; Li, Youbin; Liu, Hongrong; Zeng, Songjun; Hao, Jianhua (iScience, 2019)
Overexpression of endogenous H2S is one of the key characteristic in colon cancer. However, developing endogenous H2S-activated optical probes for specific diagnosis of colorectal cancer is rarely explored. Herein, an in situ H2S-activatable second near-infrared (NIR-II)-emitting nanoprobe based on Ag-chicken egg white (Ag-CEW) complex for intelligently lighting up colorectal cancer was explored. The designed Ag-CEW complex holds efficient NIR-II emission of 1,000–1,400 nm via endogenous H2S-induced in situ chemical reaction to form Ag2S quantum dots (QDs). After reaction, the designed Ag-CEW complex with high photo-stability and biocompatibility was successfully used for NIR-II imaging-guided specific visualization and precise location of colorectal cancer via endogenous H2S activation. Therefore, our findings provide a new route for specifically targeting diagnosis of colon cancer based on the in situ-activatable NIR-II probe. [Display omitted] •In situ H2S-activated Ag-CEW probe was designed for specific colon cancer diagnosis•The Ag-CEW probe triggered by H2S presents highly efficient NIR-II emission•The activatable probe can significantly improve the sensitivity of optical imaging•Ag-CEW can completely eliminate the interference signal from liver and spleen Optical Imaging; Biomolecules; Cancer